Expanding treatment options for syphilis during pregnancy: a review of alternatives to penicillin - Claire L. Townsend; Lynne Mofenson; Sami Gottlieb; Remco P. H. Peters; Oriol Mitjà; Clara Pérez-Mañá; Elaine J. Abrams; Sinead Delany-Moretlwe; Shahin Lockman; Catriona Waitt; Kathryn Miele; Melanie M. Taylor; et al. (Frontiers in Global Women's Health, 2026)
Syphilis infection during pregnancy leads to around 390,000 adverse birth outcomes each year and is an important cause of preventable stillbirth. Although benzathine penicillin G is safe and effective during pregnancy for treating maternal and fetal infection, there are frequent global shortages and limited options for people with penicillin allergy. We conducted a review of potential alternatives to penicillin for treating syphilis during pregnancy when penicillin is not available or cannot be used, including ceftriaxone, amoxicillin, doxycycline, cefixime, and linezolid. Despite some efficacy data on their use in non-pregnant adults with syphilis, limited data were available on placental transfer, pharmacokinetics and dosing, efficacy or effectiveness, and safety in pregnancy. Given its favourable preclinical reproductive toxicity data, efficacy data in non-pregnant adults with syphilis, and safety during pregnancy when used for other indications, ceftriaxone could potentially be considered as an alternative treatment for pregnant women with syphilis in cases where penicillin cannot be used, as currently recommended by the World Health Organization. However, evidence about optimal dosing, feasibility, and efficacy/effectiveness for treating syphilis during pregnancy is needed. Several planned and ongoing clinical trials will provide additional data to inform the use of cefixime, amoxicillin, and linezolid in pregnant women with syphilis. Going forward, evaluation of new and existing medications for treating syphilis and preventing congenital syphilis should include a pregnancy investigation plan. Where possible, efforts should be made to ensure that high-quality pregnancy safety and efficacy or effectiveness data on drug candidates are generated in carefully designed studies to ensure that pregnant women and their infants are able to benefit from the full range of treatment options.